Gap-filling and bypass at the replication fork are both active mechanisms for tolerance of low-dose ultraviolet-induced DNA damage in the human genome - Quinet, Annabel (2014)
Ultraviolet (UV)-induced DNA damage are removed by nucleotide excision repair (NER) or can be tolerated by specialized translesion synthesis (TLS) polymerases, such as Polη. TLS may act at stalled replication forks or through an S-phase independent gap-filling mechanism. After UVC irradiation, Polη-deficient (XP-V) human cells were arrested in early S-phase and exhibited both single-strand DNA (ssDNA) and prolonged replication fork stalling, as detected by DNA fiber assay. In contrast, NER deficiency in XP-C cells caused no apparent defect in S-phase progression despite the accumulation of ssDNA and a G2-phase arrest. These data indicate that while Polη is essential for DNA synthesis at ongoing damaged replication forks, NER deficiency might unmask the involvement of tolerance pathway through a gap-filling mechanism. ATR knock down by siRNA or caffeine addition provoked increased cell death in both XP-V and XP-C cells exposed to low-dose of UVC, underscoring the involvement of ATR/Chk1 pathway in both DNA damage tolerance mechanisms. We generated a unique human cell line deficient in XPC and Polη proteins, which exhibited both S- and G2-phase arrest after UVC irradiation, consistent with both single deficiencies. In these XP-C/Polη(KD) cells, UVC-induced replicative intermediates may collapse into double-strand breaks, leading to cell death. In conclusion, both TLS at stalled replication forks and gap-filling are active mechanisms for the tolerance of UVC-induced DNA damage in human cells and the preference for one or another pathway depends on the cellular genotype.